Developmental maturation of astrocytes and pathogenesis of neurodevelopmental disorders - Yang, Yongjie (BioMed Central, 2013)
Recent studies have implicated potentially significant roles for astrocytes in the pathogenesis of neurodevelopmental disorders. Astrocytes undergo a dramatic maturation process following early differentiation from which typical morphology and important functions are acquired. Despite significant progress in understanding their early differentiation, very little is known about how astrocytes become functionally mature. In addition, whether functional maturation of astrocytes is disrupted in neurodevelopmental disorders and the consequences of this disruption remains essentially unknown. In this review, we discuss our perspectives about how astrocyte developmental maturation is regulated, and how disruption of the astrocyte functional maturation process, especially alterations in their ability to regulate glutamate homeostasis, may alter synaptic physiology and contribute to the pathogenesis of neurodevelopmental disorders.